Apresiasi Siswa terhadap Batik Tanjung Jabung Barat dalam Pembelajaran Budaya - Yenni Rahmah; Jupriani; Syeilendra (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe students’ appreciation of Batik Tanjung Jabung Barat in cultural learning among ninth-grade students at SMP Negeri 12 Tanjung Jabung Barat. The focus of the study includes three main aspects: knowledge, attitudes, and student engagement. This study employs a descriptive approach with a mixed descriptive model, emphasizing qualitative data as the primary data supported by simple quantitative data obtained through questionnaires, observations, and interviews. The research subjects consisted of 109 students selected using purposive sampling techniques. Data analysis was conducted using descriptive qualitative methods through the stages of data reduction, data display, and conclusion drawing. The questionnaire results indicate that the overall level of students’ appreciation falls into the